2021
DOI: 10.4049/jimmunol.2000871
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a TNFR2-Selective Agonistic TNF-α Mutant and Its Derivatives as an Optimal Regulatory T Cell Expander

Abstract: Regulatory T cells (Tregs) are a subpopulation of lymphocytes that play a role in suppressing and regulating immune responses. Recently, it was suggested that controlling the functions and activities of Tregs might be applicable to the treatment of human diseases such as autoimmune diseases, organ transplant rejection, and graft-versus-host disease. TNF receptor type 2 (TNFR2) is a target molecule that modulates Treg functions. In this study, we investigated the role of TNFR2 signaling in the differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Other TNFR family members, such as 4-1BB, GITR, and DR3, but not OX40, can also increase Tregs' proliferation and survival through canonical NF-kB; TNFR2 is the most efficient among them, and the transcriptome feature of each group seems to be similar (44). Tsunoda et al reported the generation of a new TNFR2-selective agonist TNFa mutant, termed R2gaoTNF; it could expand and activate mouse CD4+ CD25+ Tregs ex vivo, which makes it a new candidate for Treg expansion (45). Another novel TNFR2 agonist antibody developed by Faustman can also expand highly potent Tregs (25,46).…”
Section: Tnfr2 Is Highly Expressed In Tregs and Essential For Functio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other TNFR family members, such as 4-1BB, GITR, and DR3, but not OX40, can also increase Tregs' proliferation and survival through canonical NF-kB; TNFR2 is the most efficient among them, and the transcriptome feature of each group seems to be similar (44). Tsunoda et al reported the generation of a new TNFR2-selective agonist TNFa mutant, termed R2gaoTNF; it could expand and activate mouse CD4+ CD25+ Tregs ex vivo, which makes it a new candidate for Treg expansion (45). Another novel TNFR2 agonist antibody developed by Faustman can also expand highly potent Tregs (25,46).…”
Section: Tnfr2 Is Highly Expressed In Tregs and Essential For Functio...mentioning
confidence: 99%
“…Tsunoda et al. reported the generation of a new TNFR2-selective agonist TNFα mutant, termed R2gaoTNF; it could expand and activate mouse CD4+CD25+ Tregs ex vivo , which makes it a new candidate for Treg expansion ( 45 ). Another novel TNFR2 agonist antibody developed by Faustman can also expand highly potent Tregs ( 25 , 46 ).…”
Section: Tnfr2 Is Highly Expressed In Tregs and Essential For Functio...mentioning
confidence: 99%
“…TNFR2 DARPins showed increased i-κB degradation in human primary Tregs and increased NF-κB activation in a Jurkat reporter cell line, which could lead to decreased suppressive functions. However, conflicting literature exists showing TNFR2 agonistic antibody or TNF-α mutant protein selectively binding to TNFR2, expand highly potent regulatory Tregs ( 43 , 44 ). Moreover, TNF-α together with IL-6 enables human Treg proliferation with sustained function and stability ex vivo ( 45 ).…”
Section: Cytokines and Treg Stabilitymentioning
confidence: 99%
“…In contrast, anti-TNFR2 signal-inducing antibodies (agonists) are pursued as therapeutic strategies to expand Tregs in autoimmunity, organ transplant rejection, and graft-versus-host disease. (9,10,(13)(14)(15). Bivalency of conventional antibody (cIgG) could produce dimer formation-related unwanted cellular responses (16).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, anti-TNFR2 signal-inducing antibodies (agonists) are pursued as therapeutic strategies to expand T regs in autoimmunity, organ transplant rejection, and graft-versus-host disease. ( 9,10,13-15 ).…”
Section: Introductionmentioning
confidence: 99%